Palladium(II) Acetate Catalyzed Cyclization–Coupling of (o-Ethynylphenyl)phosphonic Acid Monoesters with Allyl Halides - Xiao, Zecai; Peng, Ai-Yun (Synthesis, 2019)
A Pd(OAc)2-catalyzed tandem cyclization–coupling reaction of (o-ethynylphenyl)phosphonic acid monoesters and allyl halides has been developed. This reaction provides an efficient, mild, general and regioselective way to synthesize 4-allylphosphaisocoumarins.
Keywords: cyclizations; coupling; tandem reactions; palladium(II) catalysis; phosphorus heterocycles; allylation